Current Status of Aedes aegypti Insecticide Resistance Development from Banjarmasin, Kalimantan, Indonesia. (20th December 2018) - Hamid, P. H.; Ninditya, V. I.; Prastowo, J.; Haryanto, A.; Taubert, A.; Hermosilla, C.
Abstract : Aedes aegypti represents the principal vector of many arthropod-borne diseases in tropical areas worldwide. Since mosquito control strategies are mainly based on use of insecticides, resistance development can be expected to occur in frequently exposed Ae. aegypti populations. Surveillance on resistance development as well as testing of insecticide susceptibility is therefore mandatory and needs further attention by national/international public health authorities. In accordance, we here conducted a study on Ae. aegypti resistance development towards several often used insecticides, i.e., malathion, deltamethrin, permethrin, λ -cyhalothrin, bendiocarb, and cyfluthrin, in the periurban area of Banjarmasin city, Kalimantan, Indonesia. Our results clearly showed resistance development of Ae. aegypti populations against tested insecticides. Mortalities of Ae. aegypti were less than 90% with the highest resistance observed against 0.75% permethrin. Collected mosquitoes from Banjarmasin also presented high level of resistance development to 0.1% bendiocarb. Molecular analysis of voltage-gated sodium channel ( Vgsc ) gene showed significant association of V1016G gene point mutation in resistance Ae. aegypti phenotypes against 0.75% permethrin. However, F1534C gene point mutation did not correlate to Ae. aegypti insecticide resistance to 0.75% permethrin. Irrespective of periurban areas in Kalimantan considered as less densed island of Indonesia, Ae. aegypti -derived resistance to different routinely applied insecticides occurred. Our findings evidence that Ae. aegypti insecticide resistance is most likely spreading into less populated areas and thus needs further surveillance in order to delay Ae. aegypti resistance development.